Storytelling in English with Filipino Translation and Students’ Critical Thinking Skills - Olino, Mayline; Ambayon, Cristobal (Journal of Interdisciplinary Perspectives, 2025)
Critical thinking development is essential for academic and practical success yet remains a significant challenge globally and in the Philippines. The 2022 PISA results showed this problem as the Philippines placed 77th out of 81 participating countries when Filipino students received scores significantly lower than the OECD average in reading comprehension. While storytelling with translation has been proposed as a potential method to enhance critical thinking skills, limited research examines their combined effectiveness in the Philippine educational context. This study investigated the impact of English storytelling with Filipino translation on the critical thinking abilities of grade 11 students at Esperanza National High School. A true experimental design divided 90 grade 11 Humanities and Social Sciences students into control and experimental groups. Both groups completed pretests and posttests measuring critical thinking skills across five indicators: analysis, inference, evaluation, induction, and deduction. The experimental group participated in English storytelling sessions accompanied by Filipino translation, while the control group engaged in storytelling without translation. Results demonstrated that although both groups significantly improved critical thinking skills, the experimental group exhibited substantially more significant gains, with most metrics reaching "strong" status. The results show that using Filipino translation as a teaching tool effectively improves critical thinking skills when teaching through English storytelling. Teachers may integrate storytelling with translation techniques to enhance students' critical thinking skills. Future researchers may investigate this method's extended impact and use in various educational environments.